ANALISIS GENDER TERHADAP KINERJA PEGAWAI DI KANTOR SEKRETARIAT DAERAH KOTA PALEMBANG - Marleni, Marleni (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2025)
This study aims to determine the effect of Gender Analysis on Emplpyee Performance at the Regional Secretariat Office of North Palembang City. This research is a research with a totalquantative approach. The data used are primary data, with a total sample of 60 respndents, where this research was conducted for 2 months using a questionnaire to obtain the required data. Analysis of the influence of variables using simple linear regression gender analysis has a significant effect on employee performance.